1995
DOI: 10.1007/bf02111869
|View full text |Cite
|
Sign up to set email alerts
|

D-arabinitol versus mannan antigen and candidal protein antigen as a serum marker forCandida pyelonephritis

Abstract: To evaluate serum markers for the diagnosis of Candida pyelonephritis, levels of D-arabinitol, candidal mannan antigen and candidal protein antigen were measured using an enzymatic fluorometric assay, an enzyme immunoassay and a latex agglutination assay, respectively. The study group comprised 36 patients with candiduria (11 disseminated candidiasis, 9 Candida pyelonephritis and 16 colonization) and 27 without candiduria. The D-arabinitol/creatinine ratio was the only marker that differentiated between Candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Table 8 summarizes the results of several clinical studies that have evaluated D-arabinitol as a diagnostic marker for candidiasis. The early studies in which serum arabinitol concentrations were determined by GC and GC-MS (105,180), a study in which serum arabinitol/creatinine ratios were determined by GC (74), studies that used enzymatic assays to determine serum D-arabinitol/creatinine ratios (67,204,205,219) and studies that used GC-MS to determine the serum or urine D-/Larabinitol ratios (41,117,179) all support the usefulness of D-arabinitol, both as an initial diagnostic marker and for mon- (51,52,58,136). Some of these results can be explained by analytical artifacts (235), others could not be reproduced when they were examined in greater detail (232,237), and some unfavorable results remain unexplained.…”
Section: D-arabinitol In Candida Infectionsmentioning
confidence: 99%
“…Table 8 summarizes the results of several clinical studies that have evaluated D-arabinitol as a diagnostic marker for candidiasis. The early studies in which serum arabinitol concentrations were determined by GC and GC-MS (105,180), a study in which serum arabinitol/creatinine ratios were determined by GC (74), studies that used enzymatic assays to determine serum D-arabinitol/creatinine ratios (67,204,205,219) and studies that used GC-MS to determine the serum or urine D-/Larabinitol ratios (41,117,179) all support the usefulness of D-arabinitol, both as an initial diagnostic marker and for mon- (51,52,58,136). Some of these results can be explained by analytical artifacts (235), others could not be reproduced when they were examined in greater detail (232,237), and some unfavorable results remain unexplained.…”
Section: D-arabinitol In Candida Infectionsmentioning
confidence: 99%
“…Serum samples from patients suffering from fatal illnesses (none with Candida infections), with or without renal dysfunction, were subjected to this enzymatic assay, and the results correlated well with DA concentrations determined by GC ( r =0·94) [15]. To our knowledge, the only commercially available enzymatic assay is the fluorimetric test developed by Soyama & Ono [14,16].…”
Section: Methodsmentioning
confidence: 77%
“…Although the fluorimetric enzyme test [12,13] is relatively non‐specific, and the diagnostic criteria used may not be completely strict and adequate, Tokunaga et al . [16] applied this method and found elevated DA/Cr ratios in nine (82%) out of eleven patients with invasive candidiasis and in seven (78%) out of nine patients with Candida pyelonephritis. However, as many as 7 and 13% of uninfected controls and patients with asymptomatic candiduria, respectively, were false positives.…”
Section: Diagnosismentioning
confidence: 99%
“…The test was prognostic and uctuations could be used to monitor the therapeutic response. About the same time, Tokunaga et al [24] evaluated the enzymatic-uorometric kit method in patients with disseminated candidiasis, pyelonephritis, or urinary tract colonization. Their units differed from those used by Walsh et al [26], but they found elevated DA:Cr in nine of 11 (81%) patients with disseminated candidiasis.…”
Section: Enzymatic Metho D Fo R D -Arabinitolmentioning
confidence: 99%